Future expectation levels of adolescents during the COVID-19 pandemic - Küçükkelepçe, Osman; Parlak, Mehmet Emin; Öz, Erdoğan; Kapıcı, Yaşar; Ener, Dilek (Frontiers in Public Health, 2023)
Introduction: It was aimed to examine the future expectations of high school students during the COVID-19 pandemic.Methods: A future expectation questionnaire was administered to 412 high school students, and the change in their expectations for the future during the COVID-19 pandemic period was questioned in this questionnaire.Results: Scale subscores and total scores of those who had COVID-19 were significantly lower than those who did not (p<0.001). The scale sub-scores and total scores of those whose relatives had COVID-19 were significantly lower than those who did not (p<0.05). The scale sub-scores and total scores of those who think that the pandemic will always continue, those who think that their education is disrupted due to the pandemic, those who think that the pandemic affects their choice of profession, and those who express that they look to the future with more hope before the pandemic were found to be significantly lower (p<0.05).Discussion: Future expectation is a more sensitive concept in adolescents than adults. During and after the pandemic, activities should be organized by considering the sensitivity of young people about their future expectations, and families and society should be made aware of this issue.